Slowdown of solvent structural dynamics in aqueous DMF solutions - Pathania, Akhil; Bagchi, Sayan (Chemical Physics Impact, 2024)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">This study presents a comprehensive investigation into the molecular dynamics of solvation environments through an integrated approach combining Fourier-transform infrared (FTIR) spectroscopy, molecular dynamics (MD) simulations, and two-dimensional infrared (2D IR) spectroscopy. We explore the solvation of an ionic solute (ammonium thiocyanate) in various solvent systems, including N,N-dimethylformamide (DMF), water, and a 0.5 mole fraction of DMF in water, aiming to unravel the intricate interplay between solute-solvent interactions and solvent dynamics across diverse solvation environments. By integrating FTIR spectral analysis with radial distribution functions and coordination numbers obtained from MD simulations, we decipher the solvent composition around the solute molecule. Analysis of 2D IR spectra and hydrogen bond, as well as dipolar autocorrelation function from MD simulations, further elucidates the nuances of solute-solvent interactions, highlighting the impact of solvent dynamics on solvation structures. Our results reveal a significant slowdown of the solvent structural dynamics in the equimolar binary solvent mixture compared to the neat solvents. This slowdown underscores the complex relationship between solute-solvent interactions and solvent dynamics. The integration of FTIR, MD simulations, and 2D IR spectroscopy provides a unified framework for obtaining a holistic understanding of solvation dynamics, offering valuable insights into the underlying molecular mechanisms governing solute-solvent interactions in complex systems. These results pave the way for future studies to delve deeper into the molecular intricacies of solvation phenomena.